2015
DOI: 10.1021/acsmacrolett.5b00408
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-Grafted Nanoparticles with Precisely Controlled Structures

Abstract: Polymer-tethered nanoparticles with different geometric shapes are very useful fillers of polymer nanocomposites. Herein, a universal approach for the fabrication of such nanoparticles with precisely controlled shape and composition is reported. By microphase separation of poly(3-(triethoxysilyl)propyl methacrylate)-block-polystyrene (PTEPM-b-PS) in the presence of oligomers, o-TEPM (oT) and/or o-S (oS), followed by cross-linking and dispersion in PS solvent, precisely tailored PS-grafted nanoparticles were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 27 publications
1
22
0
Order By: Relevance
“…13,14,15,16 Actually, the incorporation of the grafted NPs into the polymer matrix contributes a lot in modulating the spatial dispersion of the NPs in the polymer matrices, which is promoted by the development of the synthesis techniques to controllably functionalize NPs with polymer chains. 17,18 Through the rheology analysis of polymer-grafted NPs filled polymer nanocomposites, Moll et al 13 concluded that the formation of a transient, long-lived, percolating polymer-NPs network with the NPs serving as the network junctions contributes to the maximum mechanical reinforcement. Notably, Akcora et al 19 found that the grafted spherical NPs can robustly self-assemble into a variety of anisotropic superstructures when dispersed in the corresponding homopolymer matrix, enabling considerable control for the fabrication of polymer nanocomposites with enhanced mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…13,14,15,16 Actually, the incorporation of the grafted NPs into the polymer matrix contributes a lot in modulating the spatial dispersion of the NPs in the polymer matrices, which is promoted by the development of the synthesis techniques to controllably functionalize NPs with polymer chains. 17,18 Through the rheology analysis of polymer-grafted NPs filled polymer nanocomposites, Moll et al 13 concluded that the formation of a transient, long-lived, percolating polymer-NPs network with the NPs serving as the network junctions contributes to the maximum mechanical reinforcement. Notably, Akcora et al 19 found that the grafted spherical NPs can robustly self-assemble into a variety of anisotropic superstructures when dispersed in the corresponding homopolymer matrix, enabling considerable control for the fabrication of polymer nanocomposites with enhanced mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[41] To obtain this macroinitiator, poly(ethylene oxide)m ethoxyetherw as functionalized at the chain-endw ith 2-bromo-2-methylpropionylb romide to afford poly(ethylene oxide)2 -bromo-2-methylpropionate (PEO-Br). They further extended their ATRP procedure to prepareP EO andT ESPMA based linear amphiphilic diblockP EO 45 -b-PTESPMA 69,90,162 , PEO 113 -b-PTESPMA 64 and triblock copolymers PTESPMA 40 42] With as imilar procedure, the group of He obtainedb lock copolymers with other DP,n amely PEO 45b-PTMSPMA 73,100,158 . [43] PEO-b-PTMSPMA has also been synthesized via RAFT by another group.…”
Section: Monomers/polymersbased On Ethyleneo Xide Motif For Self-assementioning
confidence: 99%
“…[19b] Moreover,t he presence of these silanes during co-assembly allowedi ns ome cases to tune the bulk morphology.T he blended MMS and CMS silanesonone hand tookpart in the self-assembly,enriching the PTESPMA phase in bulk and on the other hand formed polymer-grafted nano-objects with supplementary functionalities after ACD. By adding either oT and/or oS to PS-b-PTESP-MA, [69] the volume fractionso fP TESPMAa nd PS were tuned; thus, the ordered microphase-separated structures could be changed from one to the other.M oreover,t his approach of coassembly of oT and/oro Sw ith the diblock copolymers also allowed the fine tuning of the core shape and size of the polymer grafted nano-objects, as well as their brush length after ACD.…”
Section: Polymer-grafted (An)isotropic Nanoparticles By Assembly-crosmentioning
confidence: 99%
See 1 more Smart Citation
“…Soft colloidal particles can be thought of as hybrids interpolating between polymers and hard spheres (HSs), 1 offering a plethora of possibilities for designing systems with tunable dynamic response. Examples of spherical soft colloidal systems are vesicles, dendrimers, 2 microgels, [3][4][5] block copolymer micelles, [6][7][8][9] polymer-grafted nanoparticles (PGNPs), [10][11][12][13][14] and star polymers. [15][16][17][18][19] Unlike hard-spheres, for which the phase diagram and associated dynamic properties have been exhaustively investigated, 20 the respective consequences of softness have not been fully explored.…”
Section: Introductionmentioning
confidence: 99%